Пожалуйсто помогите решить :)
б) 2(5-х)-5(2х-3)=1 г) 44-10(3-4х)=7(5х+2)

б) (х+4)(х+6)-х(в квадрате 2)=30 г) (х-1)(х-3)=(х-2)(х-4)

1

Ответы и объяснения

Лучший Ответ!
2012-04-03T07:44:47+00:00

б) 2(5-х)-5(2х-3)=1 

   10 - 2х - 10х + 15 = 1

    - 12х = 1 -  25

    -  12х = - 24  (разделим на - 12)

      х =2 

    

г) 44-10(3-4х)=7(5х+2)

    44 - 30 + 40х = 35х + 14

    40х - 35х = 14 - 14

    5х = 0

    х = 0

б) (х+4)(х+6) - х² =30

    х²  + 6х + 4х + 24х² =  30   (сокращаем х²  и  - х²)

    10х =30 - 24   

     10х = 6

     х = 6/10

     х = 0,6

г) (х-1)(х-3)=(х-2)(х-4)

    х² - 3х - х + 3 = х² - 4х - 2х + 8     (вычитаем х² из обеих частей уравнения)

    - 4х + 3 = - 6х + 8

    6х - 4х = 8 - 3

    2х = 5

    х = 5/2

    х = 2,5